2008
DOI: 10.1093/nar/gkn952
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations in Moloney Murine Leukemia Virus reverse transcriptase increase thermostability through tighter binding to template-primer

Abstract: In an effort to increase the thermostability of Moloney Murine Leukemia Virus reverse transcriptase (MMLV RT), we screened random and site-saturation libraries for variants that show increased resistance to thermal inactivation. We discovered five mutations E69K, E302R, W313F, L435G and N454K that collectively increase the half-life of MMLV RT at 55°C from less than 5 min to ∼30 min in the presence of template-primer. In addition, these mutations alter the thermal profile by increasing specific activity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
68
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 29 publications
5
68
1
Order By: Relevance
“…Ala enhanced the intrinsic thermal stability of MMLV RT rather than the affinity toward T/P, differently from the case of the five mutations discovered by Arezi et al 10) Why does the intrinsic thermal stability of MMLV RT increase due to a loss of RNase H activity? Goedken et al expressed the RNase H domain of MMLV RT (Pro515-Leu671) in E. coli and examined its reversible unfolding by circular dichroism, having found that the midpoint temperatures of the variants D524N and D583N (the catalytically important residues of RNase H activity, Asp524 and Asp583, are replaced with Asn) were higher by 10 C than those of WT and other variants in the presence of Mg 2þ .…”
contrasting
confidence: 58%
See 2 more Smart Citations
“…Ala enhanced the intrinsic thermal stability of MMLV RT rather than the affinity toward T/P, differently from the case of the five mutations discovered by Arezi et al 10) Why does the intrinsic thermal stability of MMLV RT increase due to a loss of RNase H activity? Goedken et al expressed the RNase H domain of MMLV RT (Pro515-Leu671) in E. coli and examined its reversible unfolding by circular dichroism, having found that the midpoint temperatures of the variants D524N and D583N (the catalytically important residues of RNase H activity, Asp524 and Asp583, are replaced with Asn) were higher by 10 C than those of WT and other variants in the presence of Mg 2þ .…”
contrasting
confidence: 58%
“…Lys) that stabilized MMLV RT in the presence of the T/P, but not in its absence. 10) In the reverse transcription reaction, the K m value for the T/P of the variant with these five mutations was 10% of that of MMLV RT without them. These findings suggest that the five mutations enhanced the binding ability of MMLV RT to T/P rather than intrinsic thermal stability.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…We think that the thermostable multiple MMLV RT variants that we 8) and others 6,7) have generated and which we generated in this study are more valuable for various research projects, including transcriptome analysis and clinical diagnosis, than wild-type MMLV RT. However, without a precise comparison of fidelity and processivity, it is difficult to determine which variant is the most suitable.…”
mentioning
confidence: 91%
“…1,[75][76][77][78] constructed in which one of these five residues was replaced with Arg or Lys. C-terminal (His) 6 -tagged variants were expressed in Escherichia coli and purified from the cells by a method described previously. 14) Following SDS-PAGE under reducing conditions, the purified enzyme preparations yielded a single band with a molecular mass of 75 kDa ( Fig.…”
mentioning
confidence: 99%